2011
DOI: 10.1002/dvg.20762
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in C. elegans: Facts and challenges

Abstract: Epigenetics is defined as the study of heritable changes in gene expression that are not accompanied by changes in the DNA sequence. Epigenetic mechanisms include histone post-translational modifications, histone variant incorporation, non-coding RNAs, and nucleosome remodeling and exchange. In addition, the functional compartmentalization of the nucleus also contributes to epigenetic regulation of gene expression. Studies on the molecular mechanisms underlying epigenetic phenomena and their biological functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 125 publications
1
64
0
1
Order By: Relevance
“…Within the nuclei of cells there are areas of transcriptionally active DNA (euchromatin) and areas of transcriptionally inactive DNA (heterochromatin). In C. elegans, electron microscopic studies have found that heterochromatin contains regions with high levels of repressive marks: di-and tri-methylated core histone H3 at lysine 9 and 27 (H3K9me2/3 and H3K27me3), while regions of the euchromatin are enriched for core histone H3 demethylated at lysine 4 (H3K4me2) (Wenzel et al, 2011). This pattern is similar to what has been found in Drosophila and mammals.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Within the nuclei of cells there are areas of transcriptionally active DNA (euchromatin) and areas of transcriptionally inactive DNA (heterochromatin). In C. elegans, electron microscopic studies have found that heterochromatin contains regions with high levels of repressive marks: di-and tri-methylated core histone H3 at lysine 9 and 27 (H3K9me2/3 and H3K27me3), while regions of the euchromatin are enriched for core histone H3 demethylated at lysine 4 (H3K4me2) (Wenzel et al, 2011). This pattern is similar to what has been found in Drosophila and mammals.…”
supporting
confidence: 72%
“…What other mechanisms are yet to be uncovered? This review has only covered a subset of the research on mechanisms of transgenerational epigenetics that has been done using C. elegans; more detailed reviews can be found elsewhere (see Bagjin et al, 2012;Benayoun and Brunet, 2012;Billi et al, 2013;Brasset and Chambeyron, 2013;Kelly, 2014;Feng and Guang, 2013;Lim and Brunet, 2013;Vella and Slack, 2005;Wenzel et al, 2011). This is a rich field of study, and it is clear that C. elegans offers unique opportunities to rapidly uncover the molecular machinery regulating this amazing process.…”
Section: Discussionmentioning
confidence: 99%
“…Also interesting is the finding of the crosstalk between 6ma and histone methylation, which enhances the possibility of both mechanisms in transferring epigenetic information [40]. A further mechanism also found in C. elegans that may be involved in epigenetic modulation is through the polycomb group protein complex (PcG), associated with maintaining the so-called 'developmental memory', which is a memory of transcriptional states for important developmental genes [39]. With a range of mechanisms potentially contributing to the retention of sensitivity, further work is clearly warranted to investigate the range of mechanisms possibly involved.…”
Section: Discussionmentioning
confidence: 97%
“…A study in mice strengthened the evidence showing that microRNA from sperm, which was injected into normal fertilized eggs, could transmit tail color variation to the next generation (30). Another possible mechanism to explain paternal effects is histone modification (31). It was recently demonstrated in C. elegans that histone modifications can be maintained in parental germ lines (32,33), carried into the progeny (33), and can persist over generations (22).…”
Section: Discussionmentioning
confidence: 91%